Humoral response to a 13-valent pneumococcal conjugate vaccine in kidney transplant recipients. Issue 17 (9th April 2020) - Oesterreich, Simon; Lindemann, Monika; Goldblatt, David; Horn, Peter A.; Wilde, Benjamin; Witzke, Oliver
Abstract: Background: Vaccination against S. pneumoniae is recommended by national guidelines. Moderate immunogenicity of the 13-valent pneumococcal conjugate vaccine (PCV13) has been reported in adult kidney transplant recipients (KTR). This study further defines the immunogenicity of PCV13 in this cohort. Methods: 49 KTR were immunized with PCV13. A validated opsonophagocytic killing assay (OPA), a global anti-pneumococcal capsular polysaccharide (anti-PCP) IgG, IgG2, IgM and IgA ELISA, and - for selected patients - a serotype specific anti-PCP WHO reference ELISA were performed pre-vaccination and at month 1 and 12 post-vaccination. Results: Geometric mean OPA titers increased significantly for 13/13 serotypes at month 1 and for 10/13 serotypes at month 12 post-vaccination. Vaccine response defined as an OPA titer ≥1:8 was reached in 9/13 serotypes (median). 53% reached the vaccine response criteria at month 1 and 45% at month 12. At month 1 after vaccination, the median OPA titer in an age-group matched healthy reference population was 5- to 10-fold higher than in KTR. OPA titers correlated strongly with results to the global and serotype specific anti-PCP IgG ELISA. Lower OPA titers significantly (p < 0.05) correlated with albuminuria, an interval between vaccination and transplantation <12 months, age and treatment with mycophenolate mofetil. Global IgG, IgG2, IgM and IgA, as well as serotype specific anti-PCP antibody concentrations (12/13 serotypes) increased significantly at month 1 and 12 post-vaccination. Conclusions: Kidney transplant recipients show a significant humoral response after vaccination with PCV13. Functional antibody response exists, but is not as vigorous as in healthy adults.